Measurements of the production cross-section for a Z boson in association with b-jets in proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (Journal of high energy physics, 2020)
This paper presents a measurement of the production cross-section of a $Z$ boson in association with $b$-jets, in proton-proton collisions at $\sqrt{s} = 13$ TeV with the ATLAS experiment at the Large Hadron Collider using data corresponding to an integrated luminosity of 35.6 fb$^{-1}$. Inclusive and differential cross-sections are measured for events containing a $Z$ boson decaying into electrons or muons and produced in association with at least one or at least two $b$-jets with transverse momentum $p_T>$ 20 GeV and rapidity $|y| < 2.5$. Predictions from several Monte Carlo generators based on leading-order (LO) or next-to-leading-order (NLO) matrix elements interfaced with a parton-shower simulation and testing different flavour schemes for the choice of initial-state partons are compared with measured cross-sections. The 5-flavour number scheme predictions at NLO accuracy agree better with data than 4-flavour number scheme ones. The 4-flavour number scheme predictions underestimate data in events with at least one b-jet.
The ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, F. Bartels, A.E. Bolz, M.M. Czurylo, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, M. Klassen, A. Krishnan, A. Kugel, H. Meyer Zu Theenhausen, T. Mkrtchyan, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, J. Wang, S.M. Weber, M. Wessels, X. Yue [und 2927 weitere Autoren]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 09.04.2021